The effect of sex steroids on the aortic endothelium of rats with thermal injury - (:unkn) unknown (My University, 2003)
Objective: Thermal injury-induced physiopathological events are related to an acute inflammatory reaction. This study was designed to observe the role of sex steroids on the aortic endothelia of rats with burn injury. Methods: Male Wistar Albino rats were given burn trauma (n=30), and the rats were injected subcutaneously with either 17β estradiol benzoate (E2, 10mg/kg) or an androgen receptor blocker cyproterone acetate (CPA, 25 mg/kg) or vehicle immediately after the burn and at 12 h. At the 24th hour of burn injury, the rats were decapitated. Blood samples to measure serum TNF levels were collected. The aortas of the rats were processed for both light and scanning electron microscopy. Student's t test was used for statistical analysis. Results: Antiandrogen and E2 treatments depressed burn induced elevation in serum TNF levels. Both light and electron microscopy revealed a morphology in accordance with TNF results. The endothelia of aortas were preserved significantly better than in the vehicle group. The adhesion of blood cells on endothelium was reduced in the antiandrogen or E2 - treated groups. Conclusion: In conclusion, we may predict that treatment with estrogens or antiandrogens may have an ameliorating effect on systemic inflammation induced by burn.
Keywords: Aorta; Burn injury; Microscopy; Sex steroids